Investigating Brand Awareness During Covid-19 Pandemic in The Malaysian Hotel Industry - Haziqah Fatinah Sulaiman; Daria Gom; Mary Monica Jiony (Penerbit UMS, 2022)
This research aims to investigate brand awareness during the COVID-19 pandemic in the Malaysian hotel industry. It specifically focuses on how brand awareness among Malaysian consumers during the COVID-19 pandemic is influenced by customer engagement and perceived quality. The population of the research consists of the customers who have patronised any hotels in Malaysia. In this research, quantitative method has been used and research data has been obtained via online questionnaires shared on social media. Convenience sampling method was applied and a total of 211 questionnaires were collected. To test the hypotheses, the social science statistical package (SPSS) version 27 was used. The findings clearly demonstrated that brand awareness among Malaysian customers during the COVID-19 pandemic is positively influenced by perceived quality and customer engagement. This study extends the limited literature on hospitality in the Malaysian hotel industry. Additionally, these findings have implications for improving customer engagement, perceived quality, and brand awareness in order to retain customers and gain a competitive advantage.